Laser ignition of energetic crystals of cyclotrimethylenetrinitramine (RDX) optically sensitized with gold nanoparticles and light-absorbing dye - Fang, Xiao; Wells, Andrew (Elsevier, 2025)
Laser ignition of energetic materials has shown promise in eliminating sensitive primary explosives to initiate a main explosive charge. To enhance the laser ignitibility of energetic material cyclotrimethylenetrinitramine (RDX) with a near-infrared diode laser, the RDX was re-crystallized with three optical sensitizers: COOH-PEGylated gold nanorods (both solution and dry gold nanoparticle) and laser absorbing dye. Optical microscopy was undertaken on the crystals to investigate the uniformity of doping of the optical sensitizers. High-speed video was used to experimentally observe the enhanced laser ignitability of these RDX crystals. The solution gold nanoparticles enhanced doping uniformity resulting in it being an effective optical sensitizer. Compared to the other two optical sensitizers, the solution gold nanoparticles optical sensitizer significantly enhanced the laser ignitibility of RDX by reducing the required power density to as little as 79 Wcm−2 to achieve ignition. At this laser power density, the ignition delay was approximately 68 ms.
Keywords: Optoelectronics & Photonics; 40 Engineering; 46 Information and computing sciences